Математика в КПІ у 60-80 рр. ХХ ст. - Добровольський, В.О. (Питання історії науки і техніки, 2008)
Статья представляет собой очерк преподавания и развития математических исследований, проведенных многими сотрудниками математических кафедр Киевского политехнического института за весьма продуктивный период 60-80 гг. ХХ в. The article represents an essay of teaching and development of the mathematical researches were leading by many employees of mathematical faculties of the Kiev polytechnical institute for rather productive period of the 60-80-th of the XX-th century.